Resiliensi Usaha Kuliner pada Masa Pandemi COVID-19: Studi Kasus di Sanur, Bali - Proboningrum Hapsari; M. Baiquni (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Sanur tourism area as an international tourism area in Denpasar City, Bali, was experiencing a decrease of tourist visit due to the COVID-19 pandemic. Culinary business was one of the sectors affected severely by the pandemic. This study therefore aimed to analyze the resilience strategies in facing the pandemic and its relations to sustainability using a descriptive qualitative method by primary data sources from interviews and observation. The study found out that the COVID-19 pandemic caused a decrease in the number of tourist visit as culinary businesses customers, that in turns had a big impact on expenses, workforce, and hours of operation of the culinary business. Various efforts was made by culinary business actors to be resilient during the COVID-19 pandemic by adaptation, innovation, strengthening networks, and sustainability planning. These efforts also supported achieving sustainable tourism in Sanur tourism area, especially in management sustainability, economic sustainability, socio-cultural sustainability, and environmental sustainability